Optimasi Formulasi, Stabilitas Fisik dan Uji Iritasi Lotion Tabir Surya Kombinasi Benzophenone-4 dan Octocrylene - Yuli Ainun Najih; Yuyun Nailufa; Dita Nurlita Rakhma; Davan Ercha Wafi Azhanzi; Farid Zulkarnain Nur Syah (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2026)
Ultraviolet (UV) radiation exposure necessitates the creation of sunscreen formulas that are stable, safe for the skin, and photoprotective. Although benzophenone-4 (BZP-4) and octocrylene (OCT) are widely used as chemical UV filters, studies on the physical stability and irritation of optimizing the combination of the two in lotion formulations are still limited. The purpose of this study is to improve the physical stability, formulation, and irritation testing of a sunscreen lotion that combines BZP-4 and OCT. Variations in single and combination concentrations (1–5%) were included into five formulations. Organoleptic testing, pH, viscosity, spreadability, adhesion, emulsion type, physical stability using centrifugation and six cycles of testing, and irritation testing based on a non-animal alternative method using the Hen's Egg Test–Chorioallantoic Membrane (HET-CAM) were all used to evaluate the preparations. A paired t-test was used for statistical analysis to compare parameters prior to and during the physical stability test. The combination formula of 1% BZP and 1% OCT produced the best physical properties (pH 6.44; viscosity 2793 cP), was stable in centrifugation and cycle tests (p>0.05), and did not irritate the skin (HET-CAM score 0.98±0.04). Conversely, single formulas and high concentrations showed moderate to strong irritation. The results of this study contribute scientifically to the conclusion that the combination lotion formulation of BZP-4 1% and OCT 1% has good physical stability and does not cause irritation.